Biomimetic sensor for detection of hydrochlorothiazide employing amperometric detection and chemometrics for application in doping in sports - Ruy, Mayara R. S. [UNESP]; Figueira, Eduardo C. [UNESP]; Sotomayor, Maria D. P. T. [UNESP] (Sociedade Brasileira de Quimica (SBQ), 2015)
This work describes a simple and cost-effective method for quantitative determination of hydrochlorothiazide using biomimetic sensor based on a carbon paste modified with hemin (biomimetic catalyst of the P450 enzyme). The sensor was evaluated using cyclic voltammetry and amperometry for its electrochemical characterization and quantification, respectively. Amperometric analyses were carried out at 800 mV vs. Ag/AgCl (KClsat ), using a 0.1 mol L-1 phosphate buffer solution at pH 8.5 as the support electrolyte. Optimization of the experimental parameters was performed using a multivariate methodology. The proposed method was successfully applied to the analysis of hydrochlorothiazide in spiked urine and pharmaceutical formulations, demonstrating that it is a reliable, feasible and efficient alternative method for the detection of hydrochlorothiazide in doping and can also be used for the quality control method.
Keywords: Biomimetic sensor; Doping; Hemin; Hydrochlorothiazide; P450 enzyme